Problems in teaching and learning English online during the Covid-19 pandemic - Siti Wulandari; Sofyan A Gani; Asnawi Muslem (English Education Journal, 2022)
The coronaviruses (Covid-19) pandemic has spread rapidly worldwide, including the education sector. The policy toward the study from home during the Covid-19 outbreak caused a new problem in the teaching and learning system. The objectives of the research were to find out and describe the problem faced by the teachers in conducting online learning during the Covid-19 pandemic. This is a qualitative method approach. The research subjects are three English teachers. The data was gathered through observation and interviews from three English teachers at SMA Negeri 4 Banda Aceh. Some of the problems emerged during online learning, nine problems. The arisen of teaching problems were: internet access, disability in accessing technology, difficulty in explaining the materials, flexibility in controlling and managing students' activities, indiscipline, time-consuming, lack students' motivation, students absent in online class, and the last parents support system. The findings showed that there are two solutions to overcome the problems by teachers, namely, applying online chat of WhatsApp and keeping the interaction with the students' parents to support the student activities and explain the lesson plans while online learning teaching and learning process.